Crossover of resources within formal ties: How job seekers acquire psychological capital from employment counselors - Corinna Vera Hedwig Schmidt; Tessa Christina Flatten (Journal of Organizational Behavior, 2021)
Unemployed job seekers experience stress which impedes their job search. Research suggests that psychological capital is a key resource which enables job seekers to cope with their stress. Yet it is still unclear how they acquire this key resource. During job search, job seekers engage in task-oriented, infrequent interactions with counselors in employment agencies and establish formal ties. We explore these largely neglected formal ties and draw on conservation of resources theory and the crossover model to show that psychological capital crosses over from counselors to job seekers. We examine 209 dyads collected from two sources—counselors and job seekers—in an employment agency in Germany. Our hierarchical linear modeling results support the crossover of psychological capital within formal ties: Our results indicate that counselors' psychological capital impacts job seekers' psychological capital, which in turn lowers their stress. This relationship is mediated by job seekers' perception of counselors' social support. This study advances research on job loss and the crossover model as it explains the transfer of key resources within an institutional context characterized by formal ties, and it reveals social support as underlying mechanism. The practical implication is that counselors serve as enablers transferring key resources to job seekers.
Keywords: 650; crossover model; dyadic multilevel research; formal ties; job seeker; psychological capital